Synthesis of ethyl furfuryl ether (potential biofuel) by etherification of furfuryl alcohol with ethanol over heterogenized reusable H1Cs2PW12O40 catalyst - Mulik, Nagesh L.; Niphadkar, Prashant S.; Bokade, Vijay V. (Research on Chemical Intermediates, 2020)
{Ethyl furfuryl ether (EFE) considered as potential biofuel can replace petroleum diesel up to 100%. EFE also has efficient blending properties with biodiesel to improve its cold flow properties. Herein we demonstrate efficient synthesis of EFE by etherification of renewable furfuryl alcohol (FAlc) with ethanol over heterogenized heteropoly acids. Cs-exchanged heterogenized heteropoly acid (H3-xCsxPW12O40
Keywords: B; etherification; Ethyl furfuryl ether; Furfuryl alcohol; H3-xCsxPW12O40; Heterogenized heteropoly acid; L ration